Improvement of the recycling of plastics in lightweight packaging treatment plants by a process control concept. Issue 2 (February 2019) - Feil, Alexander; Coskun, Erdogan; Bosling, Marcel; Kaufeld, Sebastian; Pretz, Thomas
In Germany, only approximately 30% by mass of plastics from lightweight packaging waste is recycled; 65% by mass is transferred to inferior residual fractions (sorting residue and mixed plastics), which are currently only utilized thermally. An increase in the recycling of valuable resources in the sense of material recycling would both contribute to the saving of resources and improve the economic situation of plant operators. It is generally known from operating and planning experience that fluctuation in the amount of material loaded into the sorting process is one of the main reasons for suboptimal recycling quotas. In particular, overfilling in the input stream leads to a deterioration of the separation result of the entire process. A novel process control concept envisages equalizing the material flow in such a way that all separation steps are operated in the intended design range. For the example of a lightweight packaging treatment process, the requirements and technological solutions for a sensor-based process control concept will be presented.